Current research on ecotoxicity of metal-based nanoparticles: from exposure pathways, ecotoxicological effects to toxicity mechanisms - Wang, Fang; Zhou, Li; Mu, Dehong; Zhang, Hui; Zhang, Gang; Huang, Xiangming; Xiong, Peizheng (Frontiers in Public Health, 2024)
Metal-based nanoparticles have garnered significant usage across industries, spanning catalysis, optoelectronics, and drug delivery, owing to their diverse applications. However, their potential ecological toxicity remains a crucial area of research interest. This paper offers a comprehensive review of recent advancements in studying the ecotoxicity of these nanoparticles, encompassing exposure pathways, toxic effects, and toxicity mechanisms. Furthermore, it delves into the challenges and future prospects in this research domain. While some progress has been made in addressing this issue, there is still a need for more comprehensive assessments to fully understand the implications of metal-based nanoparticles on the environment and human well-being.